Current status and molecular phylogeny of some economically important viruses infecting wheat crops of Şırnak province, Turkey - Kapan, Orhan; Usta, Mustafa; Güller, Abdullah (Emirates Journal of Food and Agriculture, 2023)
A survey of yellow dwarf viruses (YDVs) -associated diseases of wheat plants was performed for the first time in the Şırnak Province, Turkey. In plants wheat cultivated areas, symptoms such as diminished leaf size, dwarfing, yellowing, and reddening of leaves wheat plants were observed in cultivated areas. A total of 441 specimens were collected regardless of showing symptoms and assayed for Barley/Cereal Yellow Dwarf Viruses [B/CYDV] association by PCR tests using virus coat protein gene (CPG)-specific primer pairs. These assays demonstrated that 13.38% (55 samples) were positive to the occurrence of BYDV-PAV (9.73%) and CYDV-RPV (0.73%) for wheat viruses, but no BYDV-MAV, -SGV, and -RMV infections of BYDVs were found in PCR assays of collected samples. In addition, double infection of BYDV-PAV and CYDV-RPV was detected in 12 samples with a 2.91% infection rate. The CPG sequences of randomly selected two isolates were revealed using bacterial cloning and sequencing. Sequences obtained were deposited in GenBank under Accession numbers OL685734 and OL685736 for BYDV-PAV; and OL685735 and OL685737 for CYDV-RPV. BLASTn analysis of CPG sequences of four isolates shared high nucleotide homology with their intraspecies isolates, with 97.35-98.67% for two BYDV-PAV and 97.72-97.89 for two CYDV-RPV. The consensus tree constructed classified B/CYDV-associated wheat viruses with their phylogenetically closest individuals from Turkey and the world. This survey is the first report of BYDV-PAV and CYDV-RPV associated with wheat plants in Şırnak Province of Turkey. Keywords: BYDVs; Coat protein gene; Incidence; Sequencing; Şırnak